Studies on germination and seedling vigour characters for genotype selection in nutmeg (Myristica fragrans Houtt.) - V S Sawant, A J Kelaskar, P M Haldankar, G D Joshi, B M Jamadagni, (Journal of Spices and Aromatic Crops, 2005)
An experiment was conducted at Ratnagiri (Maharashtra) to study the regeneration ability and variability of 34 nutmeg (Myristica fragrans) seedling genotypes. The variations recorded for germination percentage, period required for germination and seedling growth parameters were significant. Higher magnitudes of genotypic coefficient of variation, phenotypic coefficient of variation, heritability and genetic advance on per cent mean basis were recorded for fresh seed weight, germination percentage, days for germination and root length. The selection of nutmeg genotypes at seedling stage on the basis of vigour of the characters such as number, length and breadth of leaves, collar thickness and petiole length would help to identify genotypes for propagation. Among the genotypes studied, N22, N24, N26, N29, N34, N37, N38, N42, N43, N51, N63 and N72 were promising.